Abernethy malformation: A rare presentation in the elderly (Indian Journal of Case Reports, 2018)
Abernethy malformation or congenital extrahepatic portosystemic shunt is a rare clinical entity, and its initial manifestation in adults is still rarer. Here, we report the case of a 68-year-old male who presented with encephalopathy and got admitted to the ICU. All the regular radiologic and metabolic workups for encephalopathy were negative except for high ammonia. Further, evaluation with contrast-enhanced computed tomography of abdomen showed hypoplastic portal vein with a large portacaval shunt, suggestive of type 2 Abernethy malformation. The encephalopathy associated with hyperammonemia improved with anti-encephalopathy measures.